Experimental Study of the Effect of Bilge Keels Position as Roll Damping Devices on the Resistance of LCU Vessels. Issue 1 (1st September 2022) - Sumarsono,; Cahyono, Beny; Erwandi,; Ali, B.; Baidowi, A.
Abstract: Landing Craft Utility (LCU) is one type of ship whose role is to transport combat equipment vehicles and amphibious troops to make landings on the beach. On the ship, bilge keels were installed. However, the installation of bilge keels on the surface of the ship's hull will add resistance to the ship's speed. To find out the effect of placing bilge keels on the additional ship speed resistance, a towing test experiment was carried out in the towing tank using the LCU ship model. Two bilge keels were manufactured in 4 (four) different positions, called A, B, C, and D positions. From the results of the study, it is known that the average value of the addition to the total resistance is; at A position there is an increase in ship speed resistance of 3.22%, at B position by 3.36%, at C position by 2.67%, and at D position by 1.83% of the total resistance in bare hull conditions. The results of this study indicate that the placement of bilge keels with the same shape and dimensions can add to different total resistances.